2011
DOI: 10.2463/mrms.10.169
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Hydrogen-rich Water against Gentamicin-induced Nephrotoxicity in Rats using Blood Oxygenation Level-dependent MR Imaging

Abstract: Purpose: We assessed intrarenal oxygenation in gentamicin-induced nephrotoxicity (GIN) and the protective eŠect of hydrogen-rich water (HW) against GIN using blood oxygenation level-dependent magnetic resonance (MR) imaging.Materials and Methods: We acquired T 2 * -weighted images (T 2 * WI) of 21 rats on Days 0, 2, 4, and 7 using a 1.5-tesla MR imaging system. The rats were divided into 3 groups of seven each: control rats had free access to standard water and no gentamicin (GM) injection; rats designated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It has also been shown that magnetized water administration can reduce blood glucose level and improve the antioxidant status and lipid profiles in the heart, spleen, and lung of streptozotocin-induced diabetic rats [ 19 ]. Furthermore, magnetized water has been used to rescue cisplatin-induced nephrotoxicity [ 21 , 22 ], ferric-induced nephrotoxicity [ 23 ], and gentamicin-induced nephrotoxicity [ 24 ]. Even more, drinking magnetic water may have a useful role in inhibiting blood parameter disorders of type 2 diabetes mellitus [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that magnetized water administration can reduce blood glucose level and improve the antioxidant status and lipid profiles in the heart, spleen, and lung of streptozotocin-induced diabetic rats [ 19 ]. Furthermore, magnetized water has been used to rescue cisplatin-induced nephrotoxicity [ 21 , 22 ], ferric-induced nephrotoxicity [ 23 ], and gentamicin-induced nephrotoxicity [ 24 ]. Even more, drinking magnetic water may have a useful role in inhibiting blood parameter disorders of type 2 diabetes mellitus [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of hydrogen rich water on gentamicin induced nephrotoxicity was analyzed by Matsushita et al It was discovered that hydrogen rich water was able to improve renal dysfunction caused by nephrotoxicity by reducing oxidative stress as well as lowering serum creatinine (Cr) and blood urea nitrogen (BUN) when compared to control rats [26]. Positive results of hydrogen rich saline were also observed when used as a treatment after renal ischemia and reperfusion injury.…”
Section: Mechanismsmentioning
confidence: 99%
“…HRSS has also been implicated in attenuating I/R-induced renal injury ( Shingu et al, 2010 ; Wang et al, 2011 , 2014 ). Some studies have also shown that H 2 can protect the kidneys from drug injuries ( Matsushita et al, 2011 ; Katakura et al, 2012 ). It remains unknown, however, whether HRSS can facilitate renal function recovery after I/R injury in rats.…”
Section: Introductionmentioning
confidence: 99%